Respuesta :
Answer: x-intercept = 3, y-intercept = - 3.
Explanation:
1) The x-intercepts of a function are the values of x for which the function is 0
2) So, you have to solve the given liner equation when y = 0
=> x - 0 = 3 => x = 3
3) Therefore, the x-intercept is 3.
4) The y-intercepts of a relation are the values of y for which x = 0
5) So you have to solve 0 - y = 3
=> y = - 3
6) Therefore, the y-intercept is - 3.
Answer: 3 and - 3.
Explanation:
1) The x-intercepts of a function are the values of x for which the function is 0
2) So, you have to solve the given liner equation when y = 0
=> x - 0 = 3 => x = 3
3) Therefore, the x-intercept is 3.
4) The y-intercepts of a relation are the values of y for which x = 0
5) So you have to solve 0 - y = 3
=> y = - 3
6) Therefore, the y-intercept is - 3.
Answer: 3 and - 3.
Answer:
x-intercept = 3
y-intercept = - 3.
Explanation:
It was correct on edge